Heritage for tourism: the influential factors, a lesson from Groningen, the Netherlands to Banda Aceh, Indonesia - Dewi, Cut (2008)
The heritage tourism is not a footloose industry that can be built every where. However, it is more product of culture in specific place, time, and condition. By changing the context, the heritage has to adjust, therefore the more adaptation of heritage to change the longer its existence. This paper wants to discuss the influential factors of reuse heritage for tourism. It depends very much on internal and external factors. The internal factors are conservation factor, tourism factor, local context, and heritage condition and the external factor is a move of the attraction and market from beach (natural attractions) to heritage (cultural attractions) as a crucial product carrying multiple messages in various scales. The scale of heritage as the part of internal factors plays more important role than others because the scale determines the tourism market and conservation efforts. The more world wide the heritage, the more important it is, and the more people will visit and conserve it.